Thermal performance of residential house using interlocking compressed earth brick (ICEB) as an alternative wall material - Razman, Ruzaimah (2012)
Buildings are usually designed and constructed without the concern of its impact to the environment and human comfort. Most contributes to poor thermal performance and high energy consumption. Over the years, in Malaysia, there has been an increasing interest in the use of interlocking compressed earth bricks (ICEB) - formed from stabilized earth - for masonry buildings. Due to its green characters and economical benefits, ICEB has gained wide recognition for use in the construction of building envelope systems. Since little information is available on the thermal performance characteristics of ICEB, a laboratory testing and simulation analysis was done to investigate its thermal insulation characteristics and to look at its thermal performance when applied as wall material for a residential building. Thermal properties of ICEB (k-value, R-value and U-value) were obtained by using Guarded Hot Plate Laboratory Testing. Field measurement of a sample house with fired clay brick as the wall material was undertaken over three consecutive days to confirm the existence of thermal comfort problems. Indoor environmental parameters measured include air temperature, mean radiant temperature and relative humidity; while the measured outdoor environmental parameters were air temperature and relative humidity. Thermal simulation of a sample house was done by using ECOTECT Software and results attained were compared with field measurements data for verification. For purpose of parametric study, the wall of the model was replaced with ICEB brick. This is to determine the effect of using the brick as compared to the common brick used in the real house. It has been found from the simulation that ICEB performed better thermally as compared to fired clay brick particularly during the daytime; however, due to the high thermal mass of ICEB, more heat will be released into the indoor spaces at night time. Nevertheless, the night time indoor temperature due to ICEB is still within the comfort range. It also showed that spaces with larger areas of enclosures made of materials with high k-value such as glass window and sliding door will have slightly higher indoor air temperature.